2012
DOI: 10.1128/aac.05334-11
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Tn AbaR23 Results in both Expected and Unexpected Antibiogram Changes in a Multidrug-Resistant Acinetobacter baumannii Strain

Abstract: ABSTRACTSince the 2006 discovery of theAcinetobacter baumanniistrain AYE AbaR1 resistance island, similar elements have been reported in numerous members of this species. As AbaR1 is distantly related to Tn7, we have renamed it TnAbaR1. TnAbaRtransposons are known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
6
18
0
Order By: Relevance
“…Circles, intact attC sites ("59-bp elements"); red, interrupted gene fragments; dark red, putative pseudogenes. Additional gene abbreviations follow a previous convention (59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circles, intact attC sites ("59-bp elements"); red, interrupted gene fragments; dark red, putative pseudogenes. Additional gene abbreviations follow a previous convention (59).…”
Section: Resultsmentioning
confidence: 99%
“…This smaller library is made up of two to three unique, sequence-verified mutants for most genes and is called the TnAbaR1-like island inserted in the comM gene. The TnAbaR modules are labeled according to a previous convention (59). Compared to most known comM islands, RI-1 is small and contains one rather than two copies of the Tn6018 module.…”
Section: Resultsmentioning
confidence: 99%
“…Cultivation of A. baumannii was carried out in a defined medium supplemented with either succinate or carnitine (or both) as the sole carbon source. Targeted deletion of cntA/cntB was carried out by marker exchange mutagenesis, as described previously (56). The mutants (ΔcntA; ΔcntB) were complemented with plasmid pKR706 by cloning the native carnitine oxygenase gene cluster into the …”
Section: Methodsmentioning
confidence: 99%
“…AbaR1 is integrated into the ATPase gene (now called comM) and contains a large cluster of antimicrobial and heavy metal resistance genes. Some studies have revealed diverse related AbaR resistance islands in the same region of comM in A. baumannii isolates (4)(5)(6)(7)(8). Although most AbaR resistance islands have been reported in A. baumannii isolates, recently, AbaR4 was reported in A. nosocomialis isolates from South Korea and Thailand (9).…”
mentioning
confidence: 99%